Non-linear response analyses of rectangular rigid bodies subjected to horizontal and vertical ground motion. - Taniguchi, Tomoyo (Earthquake engineering & structural dynamics.)
This investigation deals with non-linear seismic responses of free standing rectangular rigid bodies on horizontally and vertically accelerating rigid foundations. The responses are classified into two initial responses and four subsequent responses, accordingly the equations of motion governing the liftoff, slip and liftoff slip interaction motions and boundary conditions corresponding to commencement and termination of the motions are defined. The time histories of responses presented herein show that the body is sensitive to small changes in the friction coefficient and slenderness and to the wave properties and intensity of ground motions. Systematic trends are observed : the bodies on the low grip foundation avoid overturning while they are allowed to slip regardless of details of ground motions; the long period earthquakes tend to make the body overturn and slip largely. In contrast, the timing when liftoff and slip commences and terminates and their directions do not directly correspond with intensity of ground motions. Moreover, the vertical ground motion adds irregularities on the responses, since it excites or damps the responses. It is concluded that governing equations of motion and boundary conditions in view of discontinuous non-linear systems are necessary to analyse actual motions of the rectangular rigid bodies subjected to horizontal and vertical ground motion.